The Effect Of Tax Planning, Tax Avoidance, Tax Aggressiveness, and Deferred Tax Expense on Firm Value - Mizvi, Adhiya; Abukosim; Meita Rahmawati (Dinasti Research, 2025)
This research aims to empirically examine the influence of tax planning, tax avoidance, tax aggressiveness, and deferred tax expense on firm value. The population used in this study comprises LQ-45 companies listed on the Indonesia Stock Exchange from 2019 to 2023. Using purposive sampling method, a sample of 18 companies was selected, with 90 company observations derived from financial reports. Data analysis was conducted using multiple linear regression analysis with SPSS 30 as the analytical tool. The research findings indicate that partially, tax planning, tax aggressiveness, and deferred tax expense have an impact on firm value. Meanwhile, tax avoidance does not have a significant influence on firm value. Furthermore, based on the F statistical test, tax planning, tax avoidance, tax aggressiveness, and deferred tax expense simultaneously have an influence on firm value.